Two- and three-pion quantum statistics correlations in Pb-Pb collisions at √sNN=2.76TeV at the CERN Large Hadron Collider - Abelev, Betty; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Fasel, Markus; Glässel, Peter; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (Physical review. C, Nuclear physics, 2014)
Correlations induced by quantum statistics are sensitive to the spatiotemporal extent as well as dynamics of particle-emitting sources in heavy-ion collisions. In addition, such correlations can be used to search for the presence of a coherent component of pion production. Two- and three-pion correlations of same and mixed charge are measured at low relative momentum to estimate the coherent fraction of charged pions in Pb-Pb collisions at √sNN=2.76 TeV at the CERN Large Hadron Collider with ALICE. The genuine three-pion quantum statistics correlation is found to be suppressed relative to the two-pion correlation based on the assumption of fully chaotic pion emission. The suppression is observed to decrease with triplet momentum. The observed suppression at low triplet momentum may correspond to a coherent fraction in charged-pion emission of 23%±8%.
ALICE Collaboration: B. Abelev und [viele weitere]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 23.09.2020